Exploring student’s mathematical argument in solving modeling solid with curved surface problem - Ihsani, Ulynnuha Aulia; Ekawati, Rooselyna; Shodikin, Ali (Jurnal Kajian Pembelajaran Matematika, 2023)
This study aims to describe the mathematical argument of students in modeling mathematical problems with curved side shapes according to the classification of high and low initial mathematical abilities. This study used the descriptive method with the qualitative approach. Six ninth-grade students from junior high school in Surabaya were given five initial mathematics ability test questions. From the results of the initial mathematics ability test, two subjects were selected with the highest and lowest scores. Data instruments in this study use modeling solid with curved surface problem tests and interviews. The collected data were analyzed based on elements of mathematical argument, that is, claims, evidence, reasoning, and rebuttal. The result shows that subjects with high initial ability can make accurate claims, provide appropriate evidence and reason, and provide evidence to reject the counterclaim. This subject is categorized in level 2 of mathematical argumentation. While the subject with low initial ability cannot make claims accurately, the evidence and reason are unsuitable to support the claim and do not provide evidence and reasons to reject the counterclaim. This subject is categorized in level 1 of mathematical argumentation.